2006
DOI: 10.1016/j.dnarep.2006.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of vertebrate 53BP1: A major role in non-homologous end joining of DNA double strand breaks

Abstract: 53BP1 (p53 binding protein) is a BRCT domain-containing protein that is rapidly recruited to DNA double strand breaks (DSBs). To investigate the role of 53BP1 in the DNA damage response, we generated 53BP1(-/-) cells from the chicken DT40 cell line. As in mammalian cells, mutation of 53BP1 increased cellular sensitivity to ionizing radiation. Although depletion of 53BP1 resulted in checkpoint defects in mammalian cells, DT40 53BP1(-/-) cells had normal intra S phase and G2/M checkpoints. G1 specific radiosensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 29 publications
5
80
1
Order By: Relevance
“…Moreover, the function of ATM retention to chromatin is also likely to participate in DSBs repair. Both 53BP1 and SMC1 have been shown to participate in NHEJ both in vitro and in vivo (47,48,65,66). Here, we examined and found that like 53BP1 and SMC1, PTIP was involved in NHEJ, which further confirmed that PTIP functionally mediates, facilitates, and cooperates with 53BP1-ATM-SMC1 pathway for DNA DSBs repair.…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, the function of ATM retention to chromatin is also likely to participate in DSBs repair. Both 53BP1 and SMC1 have been shown to participate in NHEJ both in vitro and in vivo (47,48,65,66). Here, we examined and found that like 53BP1 and SMC1, PTIP was involved in NHEJ, which further confirmed that PTIP functionally mediates, facilitates, and cooperates with 53BP1-ATM-SMC1 pathway for DNA DSBs repair.…”
Section: Discussionsupporting
confidence: 56%
“…1C). Although 53BP1-deficient cells have been shown to have a mild sensitivity to irradiation (29), 53BP1-depleted CH12F3-2 cells did not display increased sensitivity to irradiation compared with control cells (Fig. 1D).…”
Section: Resultsmentioning
confidence: 95%
“…53BP1 accumulates at DSBs (18), and is involved in DNA repair through its essential role in nonhomologous end joining (8,19). We reasoned that the interaction between 53BP1 and methylated K810 may contribute to the role of pRb in DNA repair.…”
Section: Significancementioning
confidence: 99%